Β-Glucan Oligosaccharide Enhances CD8+ T Cells Immune Response Induced by a DNA Vaccine Encoding Hepatitis B Virus Core Antigen. (10th June 2010) - Wang, Jing; Dong, Shengfu; Liu, Chunhong; Wang, Wei; Sun, Shuhui; Gu, Jianxin; Wang, Yuan; Boraschi, Diana; Qu, Di
Abstract : DNA vaccination can induce specific CD 8 + T cell immune response, but the response level is low in large mammals and human beings. Coadministration of an adjuvant can optimize protective immunity elicited by a DNA vaccine. In this study, we investigated the effect of a synthetic glucohexaose (β -glu6), an analogue of Lentinan basic unit, on specific CD 8 + T cell response induced by a DNA vaccine encoding HBcAg (pB144) in mice. We found that β -glu6 promoted the recruitment and maturation of dendritic cells, enhanced the activation of CD 8 + and CD 4 + T cells and increased the number of specific CD 8 + /IFN-γ + T cells in lymphoid and nonlymphoid tissues in mice immunized by pB144. Immunization with pB144 and β -glu6 increased the anti-HBc IgG and IgG2a antibody titer. These results demonstrate that β -glu6 can enhance the virus-specific CTL and Th1 responses induced by DNA vaccine, suggesting β -glu6 as a candidate adjuvant in DNA vaccination.